Variasi Morfologi dan Kemelimpahan Donax faba (Bivalvia: Donacidae) di Pantai Tengket Bangkalan Madura - Dianah Filzan Alyani; Reni Ambarwati (Biotropic : The Journal of Tropical Biology, 2018)
Donax clams are important in taxonomic studies because they have many variations. The purposes of this study were to evaluate the morphological variations and the abundance of Donax clams; to analyze the habitat profiles of Donax clams at Tengket Bangkalan Madura Beach. The sample of clams were taken by belt transect method. The habitat profile was studied based on the substrate type, water acidity, substrate acidity, salinity and the temperature of water. The data was analyzed descriptive-quantitatively. The results showed that in Beach Tengket Madura found Donax faba which had 15 types. The most abundant variety was creamy with brown spots on the ventral and purplish white with brown spots. The profile of the habitat of D. faba in Tengket Beach was medium sandy substrate with water pH 6.7 and substrate pH 7, salinity 32.6-32.8‰, and temperature 32ᵒC.